TRICHOME MORPHOLOGY OF Durio zibethinus - Shamin-Shazwan, Kamaruddin; Rozilawati Shahari; Che Amri, Che Nurul Aini; Mohd Tajuddin, Nur Shuhada (International Journal of Allied Health Sciences, 2019)
Knowledge on taxonomy such as trichome morphology of plant species has been increasing greatly in recent years. Taxonomic is the science that deals with the classification of organism according to their similarity and difference. It provides significant information for a majority of the classification systems in plant classification such as Durian species. Durian is one of the popular fruits in Malaysia. Thus, this taxonomic study will be acting as a tool to complement the assessment of variation of D. zibethinusspecies. Therefore, this study aims to examine the variation of trichome morphology of D. zibethinus. Samples of Durio zibethinus were collected from Jelebu and were kept as herbarium vouchers. Observation on trichome morphology was carried out by using microscope. The result showed there is a presence of stellate hair trichome on abaxial leaf epidermis of Durio zibethinus. In conclusion, trichome morphology of D. zibethinus can be used in characterisation of D. zibethinus.